32‐3: Invited Paper: 12.1‐inch 169‐ppi Full‐Color Micro‐LED Display Using LTPS‐TFT Backplane. Issue 1 (29th May 2019) - Sugiura, Norio; Chuang, Chin-Tang; Hsieh, Chia-Ting; Wu, Chung-Tien; Tsai, Cheng-Yeh; Lin, Ching-Hsiang; Liu, Chung-Chan; Liu, Chin-Ying; Yeh, Cheng-Nan; Liu, Chu-Yu; Lin, Yu-Chieh
Abstract : 12.1‐inch 169‐ppi full‐color micro‐LED display using LTPS‐TFT backplane has been successfully developed. Blue micro‐LED, whose size is less than 30 mm, was applied with red and green conversion materials to produce full‐color images. Contrast ratio of >1, 000, 000: 1 with brightness of 700 nits was realized by the full‐color micro‐LED display for high‐dynamic‐range display applications.